The American presidents Biographies of the chief executives from Washington to Clinton - Whitney, David C.; Whitney, Robin Vaughn (Pleasantville, N.Y. : Reader's Digest Association, 2001)
Biographies of the presidents from George Washington through George W. Bush.
At head of title on cover: Reader's digest.
Includes index.
Keywords: Presidents -- United States -- Biography; United States -- Politics and government -- History